Information Retrieval 28th China Conference, CCIR 2022, Chongqing, China, September 16-18, 2022, Revised Selected Papers - Chang, Yi.; Zhu, Xiaofei (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 28th China Conference on Information Retrieval, CCIR 2022, held in Chongqing, China, in September 2022. Information retrieval aims to meet the demand of human on the Internet to obtain information quickly and accurately. The 8 full papers presented were carefully reviewed and selected from numerous submissions. The papers provide a wide range of research results in information retrieval area.
Keywords: Information storage and retrieval systems; Application software; Data mining; Artificial intelligence; Information Storage and Retrieval; Computer and Information Systems Applications; Data Mining and Knowledge Discovery; Artificial Intelligence